Required tie spacing to prevent inelastic local buckling of longitudinal reinforcements in RC and FRC elements. (1st April 2018) - Pereiro-Barceló, Javier; Bonet Senach, José L.; Albiol-Ibáñez, José R.
Highlights: Recommendations for assessing tie spacing are proposed in RC and FRC elements. A comparison between proposal and codes about required tie spacing is made. 9 HSC columns, with and without fibers, were tested to study reinforcement buckling. An analytical model to assess the buckling of reinforcements was extended. Abstract: Compressed reinforcement buckling in concrete columns can reduce ductility in structural elements. In order to avoid this, design codes propose maximum required tie spacing. Nonetheless, they do not incorporate the positive effect of concrete fibers in their formulation, whose capability of delaying buckling has been proved. For this reason, recommendations for maximum required tie spacing for elements made with concrete, with or without steel fibers, and with normal or high strength, are proposed in this article. In order to achieve this, the mixed model proposed by Pereiro-Barceló and Bonet was extended to consider elements made of HSC with and without steel fibers thanks to the results of an experimental campaign of HSC columns with and without fibers, under monotonic loading. In these tests, the buckling critical load in compressed reinforcement was experimentally determined in all the columns. In addition, a comparison of the proposed transverse concrete separation with respect to the recommendations proposed by the main existing codes was made.